Informal work, unemployment and health in Brazilian metropolitan areas, 1998 and 2003 Trabalho sem proteção social, desemprego e saúde em regiões metropolitanas brasileiras, 1998 e 2003 - Luana Giatti; Sandhi Maria Barreto; Cibele Comini César (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This study investigates whether employment with no social security, as well as short and long term unemployment are associated with worse health among Brazilians. The representative study sample was taken from two National Health Surveys and included men aged between 15 and 64 who lived in one of the eight metropolitan regions of Brazil in 1998 (n = 31,870) and 2003 (n = 32,887). Both surveys showed that full and part time workers with no social security, as well as those in short and long term (> 12 months) unemployment had worse health indicators, regardless of age or schooling, when compared with full-time workers (> 40 hours/week) who had some form of social security through their employment. Hepatic cirrhosis was the disease most strongly associated with labor market status. Its prevalence was higher among individuals in long term unemployment and those with no social security. Labor market status was also negatively associated with the use of health care services, especially medical visits. The present study shows that the absence of social security at work, unemployment and length of unemployment, characterize heterogeneous groups of individuals in relation to health. Results reinforce the need to incorporate labor market status in research into health inequalities. Este estudo investiga se trabalho sem proteção social assim como desemprego menor do que 12 meses e superior a 12 meses estão associados à pior condição de saúde. Foram estudados homens com idades entre 15 e 64 anos, residentes em oito regiões metropolitanas que participaram da Pesquisa Nacional por Amostra de Domicílios em 1998 (n = 31.870) e 2003 (n = 32.887). Comparados ao trabalho com proteção social (> 40 horas/semana), trabalho sem proteção social, e desemprego de curta e longa durações foram associados à pior condição de saúde independentemente da idade e escolaridade. Cirrose hepática foi a doença mais fortemente associada com a situação no mercado de trabalho. Sua prevalência foi mais alta entre aqueles inseridos no trabalho sem proteção e com desemprego de longa duração. A situação no mercado de trabalho também foi negativamente associada ao uso de serviços de saúde, especialmente consultas médicas. O presente estudo mostrou que a inserção no trabalho sem proteção social, o desemprego e o tempo de desemprego caracterizam grupos heterogêneos de indivíduos em relação à saúde. Resultados reforçam a necessidade de incorporar a situação no mercado de trabalho nos estudos de desigualdades em saúde.